Taphonomy as a Methodological Approach for the Study of Dog Domestication: Application to the Prehistoric Site of Peña Moñuz (Guadalajara, Spain) - Idoia Claver; Verónica Estaca-Gómez; Gonzalo J. Linares-Matás; Jesús Alberto Arenas-Esteban; José Yravedra (Heritage)
The study of early dog domestication has been the focus of considerable scholarly interest in recent years, prompting extensive research aimed at pinpointing the precise temporal and geographic origins of this process. However, a consensus among studies remains elusive, with various research efforts proposing differing timelines and locations for domestication. To address the questions related to the domestication process, researchers have employed a wide range of methodologies, including genetic, biomolecular, morphometric, paleontological, biometric, and isotopic analyses, as well as dental wear analysis to reconstruct paleodiets. Each of these approaches requires access to fossil canid specimens, given that they work directly with the skeletal remains of dogs or wolves. Alternatively, some methods can yield insights into the domestication process without necessitating the physical remains of these canids. Taphonomy, for instance, enables the study of bone surfaces for tooth marks, which may serve as indirect indicators of carnivore activity, potentially attributable to dogs or wolves. This study applies a high-resolution taphonomic analysis to bones modified by carnivores at the prehistoric site of Peña Moñuz. Our aim is to identify the specific carnivores responsible for the observed bone modifications. The findings demonstrate the efficacy of this technique in identifying the agents of bite marks, suggesting that taphonomy may complement the paleogenetic, paleontological, and isotopic methodologies traditionally used to explore the origins of dog domestication